Atomic Layer Deposition of CoxOy Films: Oxidants versus Composition. Issue 14 (15th April 2022) - Wan, Zhixin; Zhang, Teng Fei; Zeng, Zhihao; Xi, Bin
Abstract: Cobalt oxides (Cox Oy ) have shown great potential for applications in catalysts, sensors, and energy storage fields, and their performance remarkably depends on their oxidation states. Herein, Cox Oy films with precisely controlled composition are first introduced by atomic layer deposition (ALD) using bis( N, N 0‐di‐iso‐propylacetamidinato)cobalt(II) (Co(iPr2 ‐Me‐AMD)2 ) as Co precursor and H2 O/O3 as oxidants. The results show that the ALD processes using both oxidants exhibit typical self‐limiting characteristic, where cubic‐CoO films, with growth rate of 0.045 nm per cycle, are obtained at 150–200 °C using H2 O oxidant, while cubic‐Co3 O4 films, with growth rate of 0.05 nm per cycle, can be deposited at 200–225 °C using O3 oxidant. Both CoO and Co3 O4 films show dense, smooth microstructure, and good crystallinity with typical columnar crystal feature, where the Co3 O4 film shows smaller columnar size because the O3 promotes rapid nucleation with relatively higher density of nucleation sites. The thermodynamic growth mechanism of ALD process is established via density functional theory calculations, which demonstrates that the exothermic reaction path of O3 is more energetically than that of H2 O. Both films possess relatively low resistivity of ≈10 −1  Ω cm −1 with p‐type semiconductor behavior, which shows promising application potentials of these films. Abstract : Cobalt oxide (CoO and Co3 O4 ) films with good crystallinity are successfully synthesized by atomic layer deposition (ALD) using bis(N, N0‐di‐iso‐propylacetamidinato)cobalt(II) (Co(iPr2 ‐Me‐AMD)2 ) and H2 O/O3 . Both films exhibit smooth surface, good uniformity, and low resistivity. Density functional theory calculations (enthalpy change) demonstrate that the film growth is greatly affected by the oxidability of co‐reactants during the deposition process.